Art-Based Educational Research: theoretical and methodological possibilities with Dance em Science Education (Research, Society and Development, 2023)
The present study proposes a reflection on research activity in the areas of Social Sciences and Human Sciences, with the general objective of raising questions about the crystallizations present in research methodologies and methods. To do so, it carries out a theoretical study based on the assumptions of documental qualitative research. Interested in exploring new possibilities in educational research, more specifically in the Science Education’s field, it presents the methodological framework of Art-Based Educational Research (ABER) and the framework of a systematized method based on ABER itself, Artograph. Artography consists of a pedagogical and research method that presupposes the development of a creative path based on art. Among the multiple existing artistic languages, this article is based on the language of dance in the context of science teaching and, given the myriad possibilities of working with this art, it aims to appropriate the process of choreographic construction as potent for research in Sciences Education’s field. In addition to contributions that propose reflection on the researcher's role in the investigative path, it presents the Choreographic Map, a dance recording technique as a possible resource for educational research in Science Education.